1991
DOI: 10.1002/jnr.490280308
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative autoradiographic study of L‐glutamate binding sites in normal and atrophic human cerebellum

Abstract: In the present work the distribution of L-glutamate binding sites in the different layers of human cerebellum of normal individuals and of seven patients who died with olivopontocerebellar atrophy (OPCA) was examined with the technique of quantitative autoradiography. Specific L-[3H]glutamate binding was higher in the molecular than in the granule cell layer of normal cerebellar tissue. A significant decrease of L-[3H]glutamate specific binding was observed in the molecular layer of all OPCA tissues. In the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…10 Results revealed the L-glutamate binding was significantly decreased (to 30% of control) in all these patients without a change in the affinities and the pharmacologic properties of the binding sites. 42 Additional autoradiographic studies 43 showed significant decreases in quisqualate-sensitive L-glutamate binding in the molecular layer of the cerebellum. In some patients, particularly those associated with GDH abnormalities, L-glutamate binding was decreased in the granule layer as well.…”
Section: L-glutamate Receptors In Opcamentioning
confidence: 98%
“…10 Results revealed the L-glutamate binding was significantly decreased (to 30% of control) in all these patients without a change in the affinities and the pharmacologic properties of the binding sites. 42 Additional autoradiographic studies 43 showed significant decreases in quisqualate-sensitive L-glutamate binding in the molecular layer of the cerebellum. In some patients, particularly those associated with GDH abnormalities, L-glutamate binding was decreased in the granule layer as well.…”
Section: L-glutamate Receptors In Opcamentioning
confidence: 98%